Analysis of Management Accounting Use of Raw Material Management and Implementation of EMKM SAK in UMKM Sir Coffe Roasters Marelan - Riziq Agsyah; Fauzi Arif Lubis; Rahmat Daim Harahap (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the application of management accounting in raw material management and the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at the SME Sir Coffee Roasters Marelan. The study focuses on the process of planning, recording, and controlling raw materials, as well as the extent to which financial statements are prepared in accordance with the provisions of SAK EMKM. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research findings show that raw material management has been carried out simply, but has not yet implemented management accounting principles optimally, especially in the aspects of recording, planning needs, and evaluating raw material usage. The implementation of SAK EMKM has also not been fully implemented because financial recording is still limited to cash inflows and outflows without the preparation of a statement of financial position, profit and loss statement, or notes to the financial statements.